Survey with Innovations to Increase Response Rate Reveals Low Compliance with Guidelines among Youth Baseball Coaches - Including a Survey of Differences between Cities - - Yoichi Kaizu; Yuki Oyama; Yamato Ishihara; Yusuke Honma (International Journal of Sports Physical Therapy)
# Background